Melt pond ice sampling for nutrients, oxygen isotope compositions, and salinity during expedition PS122/5 (MOSAiC Leg 5) to the Central Arctic in August-September 2020 - Daiki Nomura; Ryota Akino; Alison L Webb; Yuhong Li; Manuel Dall extquotesingleOsto; Katrin Schmidt; Elise Sayana Droste; Emelia Chamberlain; Nikolai Kolabutin; Egor Shimanchuk; Ruzica Dadic; Allison A Fong; et al. (PANGAEA, 2024)
Nutrient concentrations (NO3-, NO2-, NH4+, PO43-, and Si(OH)4), water oxygen isotope compositions (δ18O), and salinity were measured for ice samples from melt pond, and water from melt pond and lead during MOSAiC Leg 5 (August and September 2020). Ice cores for the melt pond bottom ice and melt pond surface ice were collected using an ice corer (Mark II coring system, Kovacs Enterprises, Inc., Indianapolis, USA). Also, we sampled small pieces of the pond bottom ice dislodged and floated to the surface of the melt pond by poking with a ruler. After sampling ice samples, we immediately drilled holes on ice and measured ice temperatures with a needle-type temperature sensor (Testo 110 NTC, Brandt Instruments, Inc., USA). Ice cores were segmented at 10-cm intervals. Dislodged ice was cut into 0.25 m exttimes0.25 m size. All ice samples were placed into ice melting bags (Smart bags PA, AAK 5L, GL Sciences Inc., Japan) and melted in the dark at +4°C. For the discrete water sampling from the melt ponds and leads, first, we checked the vertical structure and depth of the meltwater layer from the same hole used for the RINKO Profiler (ASTD152, JFE Advantech, Japan) by attaching a conductivity sensor (Cond 315i, WTW GmbH, Germany) to a 2-m-long ruler and inserting the ruler into the lead water until the salinity measured with the Cond 315i increased at the meltwater–seawater interface. Water was pumped up with a peristaltic pump through a 2-m-long PTFE tube (L/S Pump Tubing, Masterflex, USA) at depths corresponding to meltwater (surface), the interface between meltwater and seawater (interface), and seawater (bottom). Salinity was measured at each depth by attaching a Cond 315i conductivity sensor to the bottom of the ruler. The tube intake was likewise attached to the bottom of the ruler. Ice melt water and water samples from melt pond and lead were subsampled into a 30-mL glass, screw-cap vials for later δ18O analysis, a 100-mL polypropylene bottles for salinity, and into 50-mL polyethylene screw-cap vials (Thermo Fisher Scientific Inc., Waltham, MA, USA) for later measurement of nutrient concentrations, after filtration through a 0.22-μm Durapore polyvinylidene fluoride membrane filter (MILLEX GV Filter unit, Merck Millipore Ltd., Germany). Samples for δ18O were stored at room temperature (+20°C). Salinity was measured with the same conductivity sensor used for the sea ice (Cond 315i, WTW GmbH, Germany). The samples for nutrient measurements were stored in a freezer (–20°C) before analysis. Oxygen isotope analyses were carried out with a mass spectrometer (DELTA-S Finnigan MAT, USA) at the ISOLAB Facility at AWI Potsdam by the equilibration method (details in Meyer et al., 2000; 2022). Nutrient samples were analyzed at the AWI Nutrient Facility between January and March 2021 using a Seal Analytical AA3 continuous flow auto-analyzer, controlled by AACE software version 7.09. Best-practice procedures for the measurement of nutrients were adopted following GO-SHIP recommendations (Becker et al., 2019; Hydes et al., 2010).